Dependence of specific rate constant of iodine-bromate reaction, on dielectric constant of the medium - Ahmed, M. Ghaziuddin; Uddin, Fahim (1980)
The reaction between potassium iodide and potassium bromate in the presence of large excess of sulphuric acid is a pseudo ? second order reaction. This reaction was studied at various concentrations of the reacting ions at various dielectric constants (e) of aqueous ? methanol mixtures at 30 + 0.5ºC, in order to find out the effect of dielectric constants on the specific rate constant ( k ).The values of the radius of the transient species for single and double sphere models were calculated from the linear plots of log k, against i/e . A comparison of the theoretical and experimental values of rar and r* leads to the conclusion that the activated complex could best be described by "SINGLE SPHERE' model for the reaction under consideration.